Integrated Photonic Linear Frequency Discriminator Filter for 5G Phase-Modulated Microwave Photonic Links - Charalambous, Georgios (Archīum Ateneo, 2021)
The design, fabrication and characterization of a passive linearized field discriminator (FD) filter is presented. The FD filter is designed for silicon-on-insulator (SOI) platform using foundry process design kits (PDKs). Unlike previous FD filters; the design consists of only two MZI stages. The fabrication is performed using the SiEPIC process. Limitations in the knowledge of the exact design of the PDKs; such as waveguide paths and structure are overcome by designing the device with symmetry both in the number of PDK passive components as well as optical path lengths. Excellent agreement with the theoretical results is obtained for the linearity of the transfer function; which extends over a wide bandwidth (80 GHz). The device is tested in a system evaluation simulation for a phase modulated fiber optic link and the results are compared to that of a typical intensity modulation direct detection scheme. Performance of 8 dB in carrier to intermodulation is obtained for modulating frequencies up to 50 GHz using a complementary transfer function with balanced detection demodulation scheme.